Multidimensional poverty index of marginalized orang asli in Terengganu, Malaysia - Abdullah, Muhammad Fuad; Othman, Azmah; Edo, Juli; Jani, Rohana (Universiti Putra Malaysia, 2019)
The general interpretation of poverty line index (PLI) is the measurement of poverty in Malaysia. However, by using this unidimensional poverty approach, it does not truly reflect the status of those who are poor. It is only confined to addressing the income or expenses debate, which does not reflect the actual living standards of the poor. Therefore, this study introduce the multidimensional poverty index (MPI) as an alternative method of poverty measurement. MPI is capable of identifying “Who is Poor” among the underprivileged in society. This paper aims to bridge the gap between the Orang Asli society’s development and national policy from a multidimensional perspective. By applying the MPI to the Orang Asli population in Terengganu, this study is able to reveal the factors that have deprived the poor to the point of poverty.